S-G is the expression in terms of G and S
<h3>What is the expression in terms of G and S?</h3>
Given: log_b 4 = G, log_b9 = S and log_b 9/4
To write log_b 9/4 in terms of G and S, we need to understand logarithm division rule, which states that:
When you divide two values with the same base is to subtract the exponents. Simply, the rule for division is to subtract the logarithms i.e.
logₓ (a/c) = logₓa - logₓc
Thus, log_b (9/4) = log_b 9 - log_b 4 = S - G
(Note: log_b 4 = G and log_b9= S)
Therefore, the expression log_b (9/4) in terms of G and S is S-G
Learn more about logarithm rules on:
brainly.com/question/28596566
#SPJ1
I'm confused to do you have an example
Answer:
z = √3
Step-by-step explanation:
sin (30°) = z / 2√3
z = sin (30°) 2√3
z = √3
Answer:
Step-by-step explanation:
- Initial number = 17
- Final number = 10
<u>Decrease in number:</u>
<u>Percent decrease:</u>
- 7/17*100% = 41.18% (rounded)
Answer:
jack was incorrect
Step-by-step explanation:
this is because -15 is more negatives then -10. (this is one way to look at it) the correct answer is: -10 > -15